The effect of warm-up on intermittent sprint performance and selected thermoregulatory parameters - Yaicharoen, P.; Wallman, K.; Morton, A.; Bishop, D. (Journal of Science and Medicine in Sport, 2012)
Objectives: To investigate the effect of various warm-up intensities based upon individual lactate thresholds on subsequent intermittent sprint performance, as well as to determine which temperature (muscle; Tmu, rectal; Tre or body; Tb) best correlated with performance (total work, work and power output of the first sprint, and % work decrement). Design: Nine male team-sport participants performed five 10-min warm-up protocols consisting of different exercise intensities on five separate occasions, separated by a week. Methods: Each warm-up protocol was followed by a 6 ×4-s intermittent sprint test performed on a cycle ergometer with 21-s of recovery between sprints. Tmu, Tre and Tb were monitored throughout the test. Results: There were no differences between warm-up conditions for total work (J kg-1; P = 0.442), first sprint work (J kg-1; P = 0.769), power output of the first sprint (W kg-1; P = 0.189), or % work decrement (P = 0.136), respectively. Moderate to large effect sizes (>0.5; Cohen`s d) suggested a tendency for improvement in every performance variable assessed following a warm-up performed at an intensity midway between lactate inflection and lactate threshold. While Tmu, Tre, Tb, heart rate, ratings of perceived exertion and plasma lactate increased significantly during the exercise protocols (P < 0.05), there were no significant correlations between Tmu, Tre, and Tb assessed immediately after each warm-up condition and any performance variable assessed. Conclusions: Warm-up performed at an intensity midway between lactate inflection and lactate threshold resulted in optimal intermittent sprint performance. Significant increases in Tmu, Tre and Tb during the sprint test did not affect exercise performance between warm-up conditions.